Experimental and Computational Study of the Implementation of Mpcm-Modified Gypsum Boards in a Test Enclosure - Sepulveda-Palma, F; Vasco-Calle, D; Venegas-Troncoso, T (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
The application of phase change materials (PCM) in the thermal envelope of buildings has proven to be an alternative to reduce energy consumption and to improve thermal comfort conditions. The present work evaluates the thermal behavior of gypsum boards modified with a microencapsulated PCM (mPCM) in a cubic test enclosure, considering the climatic conditions of Santiago de Chile in the September-November period of 2017. The design of the test enclosure was performed considering the minimization of parameters that affect the variation of its inner temperature and favoring the heat flow through the gypsum boards. Experimentally, the results reflect the main effects of the implementation of a mPCM, among which the displacement of the maximum heat load and the decrease in the daily oscillation of the internal temperature of the test enclosure (up to 2 °C) stand out. In addition, the mPCM modified gypsum board was thermally characterized to carry out a thermal simulation of the enclosures using EnergyPlus. The obtained numerical results agree with those obtained experimentally, including the behavior of the transient heat flux through the gypsum boards. Moreover, it was found that considering a null infiltration rate gives place to unrealistic results, suggesting that this parameter should be controlled. © 2020 by the authors.